Molecular cloning and expression study of inhibitor of dna binding 2 (id2) gene in zebrafish chromatophores development - Ling, Hua Sien (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Id is a subfamily of HLH proteins that lack the basic region present at amino-terminal which is important for DNA binding. Previous studies of id2 gene showed that the gene plays a role as transcription regulator in cell proliferation, differentiation, cell cycle control and apoptosis. There are two id2 genes namely id2a and id2b were found in zebrafish due to the genome duplication. In this research study, zebrafish was used as a model organism to study the gene expression of id2 in chromatophores development. Chromatophores are pigment cells which are derived from neural crest cell. In zebrafish, there are three types of pigment cells which include melanophores, yellow xanthophores and iridescent iridophores. Total RNA was isolated from 10 different embryonic developmental stages of zebrafish. RT-PCR was performed to determine the expression of these genes in the 10 different developmental stages. id2a is expressed in all the stages while id2b is expressed in all the stages except in 4.33 hpf. id2a and id2b had also been successfully cloned. Further study like in situ hybridization can be carried out to observe and study the expression profile of both of the genes in chromatophores development.